Efficacy and Safety of Two Different Flow Rates of Nasal High-Flow Therapy in Preterm Neonates ≥28 Weeks of Gestation: A Randomized Controlled Trial - Balasubramanian, Haribalakrishna; Sakharkar, Sachin; Majarikar, Swati; Srinivasan, Lakshmi; Kabra, Nandkishor S.; Garg, Bhawandeep; Ahmed, Javed (American Journal of Perinatology, 2021)
Objective The study aimed to compare the efficacy and safety of two different nasal high-flow rates for primary respiratory support in preterm neonatesStudy Design In this single-center, double-blinded randomized controlled trial, preterm neonates ≥28 weeks of gestation with respiratory distress from birth were randomized to treatment with either increased nasal flow therapy (8–10 L/min) or standard nasal flow therapy (5–7 L/min). The primary outcome of nasal high-flow therapy failure was a composite outcome defined as the need for higher respiratory support (continuous positive airway pressure [CPAP] or mechanical ventilation) or surfactant therapy.Results A total of 212 neonates were enrolled. Nasal high-flow failure rate in the increased flow group was similar to the standard flow group (22 vs. 29%, relative risk = 0.81 [95% confidence interval: 0.57–1.15]). However, nasal flow rate escalation was significantly more common in the standard flow group (64 vs. 43%, p = 0.004). None of the infants in the increased flow group developed air leak syndromes.Conclusion Higher nasal flow rate (8–10 L/min) when compared with lower nasal flow rate of 5 to 7 L/min did not reduce the need for higher respiratory support (CPAP/mechanical ventilation) or surfactant therapy in moderately and late preterm neonates. However, initial flow rates of 5 L/min were not optimal for most preterm infants receiving primary nasal flow therapy.Key Points
Keywords: nasal high flow; continuous positive airway pressure; respiratory distress; neonate